Transesterification of cyclic carbonates with methanol at ambient conditions over tungstate-based solid catalysts - Sankar, M.; Nair, C. Madhavan; Murty, K. V. G. K.; Manikandan, Palanichamy (Applied Catalysis A-General, 2006)
Dimethyl carbonate synthesis with 80 mol% yield is achieved through transesterification of ethylene carbonate with methanol at ambient conditions (RT and atmospheric pressure) using alkali and alkaline-earth tungstates as solid catalysts. The catalysts are efficient even at the sub-ambient temperatures. Reactions under CO2 pressure indicate that CO2 atmosphere retards the transesterification reaction completely below 100 degrees C. Experimental conditions of 150 degrees C and 3.4 MPa CO2 pressure are required to obtain maximum DMC yield of 71 mol%. Synthesis of DMC by one-pot synthesis using epoxide, CO2 and methanol is not as effective as that by two-step method with the present catalyst system. Raman and IR spectra of methanol-interacting tungstates indicate the formation of a methoxide ion species adsorbed at the catalyst surface as one possible reaction intermediates. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Dimethyl carbonate; ethylene carbonate; heterogeneous catalyst; Raman spectroscopy; sodium tungstate; transesterification